Transformação de fase induzida por deformação plástica no processo de roleteamento do aço inoxidável austenítico ABNT 304 - Diogo Azevedo de Oliveira (2022)
The goals of this work are to design and build a device to perform the burnishing of flat surfaces, additionally to perform tests to investigate the influence of the burnishing parameters (speed, number of passes and pressure) on the burnishing force, phase transformation induced by plastic deformation and the surface characteristics of AISI 304 austenitic stainless steel. The device allows burnishing of flat surfaces with reliability and satisfactory repeatability. All burnishing parameters presented significant influence on the burnishing force. The burnishing force reduced by approximately 15% at high speeds, however, the increase in the number of passes, in addition to reducing it by approximately 17%, tends to stabilize the burnishing force, whereas increasing the pressure elevates the burnishing force by a maximum intensity of 42%. X-ray diffraction analysis indicated the formation of '-martensite with significant influence of all parameters. The number of burnishing passes showed the highest statistical contribution, followed by pressure and speed. Statistical analysis showed that the increase in burnishing speed reduced the fraction of '-martensite formed by approximately 20%, possibly due to the adiabatic heat effect generated by plastic deformation. Increasing the number of rolling passes raises the '-martensite fraction by approximately 25%. Besides promoting additional plastic deformation, raising this parameter induces the formation of a refined grain layer and also the formation of deformation bands, which are preferential sites for '-martensite nucleation. Increasing the pressure increased the '-martensite fraction by approximately 25%. The surface topography was evaluated after burnishing in terms of the mean arithmetic roughness (Ra), surface texture direction, areal power spectral density (APSD), scale-sensitive fractal analysis, and continuous wavelet transform (CWT). In general, less severe plastic deformation conditions produce surfaces with anisotropic characteristics (minimum isotropy of 5%) with a well-defined spatial frequency of peaks. Increasing severity of surface deformation produced surfaces with isotropic characteristics (maximum isotropy of 80%), greater spatial dispersion of peak frequency, and greater fractal complexity. The transition from an anisotropic to an isotropic surface can occur without changes in the mean arithmetic roughness. Continuous wavelet transform (CWT) analysis of the surface indicated a dynamic variation of the plastic deformation. The isotropic surface decreases stress concentration, reduces tensile stresses, consequently delays crack nucleation and increases fatigue life.